(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the effect of irrigation solutions on surgical site infections after appendectomy, the frequency of infections was observed in wounds irrigated with either sterile saline or imipenem solution. Study Design: A Retrospective Study Place and Duration of Study: This study was conducted at the Department of Surgery, LRH Peshawar from January 2019 to December 2019. Materials and Methods: Two groups were made out of the 200 patients that were picked at random from the hospital's database. One group had 100 patients irrigate their incisions with sterile saline solution, while the other group had the other 100 patients do nothing. While one group was having their patients wash their wounds with imipenem solution, the other group was having their patients wash their wounds with imipenem solution. The purpose of the study was to examine the rate of surgical site infections between the two groups. Results: To Compared with the saline group, the imipenem group exhibited a significantly lower frequency of surgical site infections (6% compared to 13%). According to the study, this was the observed trend. Conclusion: For limiting the possibility of surgical site infections following an appendectomy, exploring the potential of using imipenem for wound irrigation is an optimistic approach, as this study recommends. Sterile saline meant for wound irrigation was utilized following the appendectomy procedure to minimize the risk of surgical site infections. The surgeon also prescribed a dose of imipenem to help prevent disease. These methods ensured that the patient received the best standard of care.